Multiple masculinities in primary caregiving situations - Hrženjak, Majda (Anthropological notebooks, 2020)
At the intersection of the feminist ethic of care and critical studies of men and masculinities, this article develops alternative interpretations of men's practices of and attitudes about care in order to contribute to the loosening of gender dualisms in the perceptions and constructions of care. Empirical evidence collected in 23 individual interviews with men carers reveals that men in specific caring situations (intensive primary care) and in non-hegemonic social locations (according to class, age, ability and sexual orientation) resist dominant norms of masculinity to some extent and, in accordance with the feminist ethic of care, establish care as genderneutral, complex, politically relevant and socially integrative disposition and activity.
Keywords: care; childrenmultiple masculinities; critical studies of men and masculinities; feminist ethic of care; feministična etika skrbi; gender; heterogene moškosti; kritične študije moških in moškosti; skrbstveno delo; spol